2000
DOI: 10.1677/jme.0.0240135
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of 17beta-hydroxysteroid dehydrogenases types 2 and 4 in human endometrial epithelial cell lines

Abstract: In the endometrium two enzymes are known to convert estradiol to its inactive metabolite estrone: microsomal 17 -hydroxysteroid dehydrogenase type 2 (17 -HSD2) and peroxisomal 17 -HSD4. In order to elucidate the particular function of each of these two different enzymes, the human endometrial epithelial cell lines HEC-1-A and RL95-2 were examined with respect to the expression of 17 -HSD isozymes. They were compared with human endometrium in vivo. Non-radioactive in situ hybridization revealed both enzymes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Detected in endometrium and endometrial epithelial cell lines [9,15]; in situ hybridization examining secretory phase endometrium only suggests mRNA present in glandular epithelium [15] Not studied Unchanged across menstrual cycle; not regulated by oestrogens or progestins in vitro [9] As for 17␤-HSD2…”
Section: Enzyme Mrna Expression Protein Expression Regulationmentioning
confidence: 99%
“…Detected in endometrium and endometrial epithelial cell lines [9,15]; in situ hybridization examining secretory phase endometrium only suggests mRNA present in glandular epithelium [15] Not studied Unchanged across menstrual cycle; not regulated by oestrogens or progestins in vitro [9] As for 17␤-HSD2…”
Section: Enzyme Mrna Expression Protein Expression Regulationmentioning
confidence: 99%
“…There are at least eleven human HSD17b isoenzymes expressed in a variety of tissues such as the ovary, placenta, uterus, liver, adipose tissue, prostate and testis(1). HSD17b Type 2 ( HSD17b2 ) and HSD17b Type 4 ( HSD17b4 ) are expressed in the uterus(2, 3) and control the last step in the formation of estrogens. These enzymes preferentially catalyze the conversion of estradiol (E2), the most potent and active form of estrogen, to estrone (E1), the inactive form of estrogen (4).…”
Section: Introductionmentioning
confidence: 99%
“…The 17β-reduction of biologically less active E 1 is catalyzed to E 2 by 17β-HSD type 1 (6), and the oxidation of E 2 to E 1 is catalyzed by 17β-HSD type 2 (7). It was reported that 17β-HSD type 1 immunoreactivity and mRNA were absent in normal and hyperplastic endometrium and in endometrial carcinoma (8,9), and 17β-HSD type 2 expression was detected in normal endometrium (secretory phase) but was decreased in hyperplastic endometrium and endometrial carcinoma (9). This is in contrast to the results of a study of these enzymes in breast cancer, in which nearly half of the cases showed 17β-HSD type 1 immunoreactivity in carcinoma cells, whereas 17β-HSD type 2 was not expressed (10).…”
mentioning
confidence: 99%